2016
DOI: 10.1002/cphc.201600927
|View full text |Cite
|
Sign up to set email alerts
|

NMR Diffusion Measurements as a Simple Method to Examine Solvent–Solvent and Solvent–Solute Interactions in Mixtures of the Ionic Liquid [Bmim][N(SO2CF3)2] and Acetonitrile

Abstract: The self-diffusion coefficients of each component in mixtures of 1-butyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide ([Bmim][N(SO CF ) ]) and acetonitrile were determined. The results suggest that the hydrodynamic boundary conditions change from "stick" to "slip" as the solvent composition transitions from "ionic liquid dissolved in acetonitrile" (χ <0.4) to "acetonitrile dissolved in ionic liquid" (χ >0.4). At higher χ , the acetonitrile species are affected by "cage" and "jump" events, as the acet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
30
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 21 publications
(38 citation statements)
references
References 76 publications
7
30
1
Order By: Relevance
“…For example, while the viscosity of the mixture will change, and as a result diffusion of solutes will change, [24] the reactions are not under diffusion control so this does not affect the rate constants. The bimolecular nucleophilic substitution reaction between triphenylphosphine 5 and each of the benzyl derivatives 2, 6-8 to give the corresponding salts 9-12, which have been examined in reaction mixtures containing the ionic liquid 4 (a R=3,5-Me-4-MeO, b R=MeO, c R=Me, d R=H, e R=Br, f R=CF 3 , g R=NO 2 ).…”
Section: Effect Of Varying the Leaving Group On The Electrophilementioning
confidence: 99%
“…For example, while the viscosity of the mixture will change, and as a result diffusion of solutes will change, [24] the reactions are not under diffusion control so this does not affect the rate constants. The bimolecular nucleophilic substitution reaction between triphenylphosphine 5 and each of the benzyl derivatives 2, 6-8 to give the corresponding salts 9-12, which have been examined in reaction mixtures containing the ionic liquid 4 (a R=3,5-Me-4-MeO, b R=MeO, c R=Me, d R=H, e R=Br, f R=CF 3 , g R=NO 2 ).…”
Section: Effect Of Varying the Leaving Group On The Electrophilementioning
confidence: 99%
“…[15] in order to evaluatet he effect of cation and anion structure on the solvation mechanism. Their results showedt hat changes in the relaxation times of 13 Cn uclei of the imidazolium cation as af unctiono fc arbohydrate concentration weres mall compared to the changesi n 35/37 Cl and 13 C relaxation rates of chloride anions and acetate anion carbons, respectively.T his suggestst hat the dissolution processi sp redominantly governed by the interactions between the ionic liquid aniona nd the carbohydrate. Self-diffusion studies of the same systems revealed that in 1-ethyl-3-methylimidazolium acetate ([EMIM][OAc]), the larger imidazolium cation, [EMIM] + , diffusesf aster than the smaller acetate anion, [OAc] À .T his behaviour suggestst hat the anions do not diffuse as isolated speciesbut as ap art of larger ion aggregates.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, also in the context of ionic liquids, PFG NMR measurements may represent a very powerful tool to investigate ion pairing. In addition, Keaveney et al . have shown that this method is also useful in understanding solvent‐solvent and solvent‐solute interactions in ionic liquids, suggesting that at high ionic liquid concentrations solvent molecules diffuse in a “cage” and “jump” fashion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional details for the kinetic analyses including temperatures, rate constants, equations used to determine the rate constants and composition of stock solutions (masses, concentrations of reagents and mole fraction of ionic liquid), rate equations and derivations can be found in the Supporting Information. [29] 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57…”
Section: Methodsmentioning
confidence: 99%